Hubungan Diversifikasi dan Risiko Perbankan di Indonesia: Apakah Usia Bank Berpengaruh? - Atmaji, Atmaji; Sarwoto, Sarwoto; Setyowati, Arum; Trinarningsih, Wahyu (Jurnal Akuntansi dan Bisnis, 2024)
Our research will examine the relationship between bank diversification and bank risk in Indonesia. We employ data from bank that registered in the Financial Service Authority (OJK) from 2013 to 2022. We find that bank diversification is associated with bank risk. Asset diversification has negative impact on credit risk, meanwhile it has not significant effect on solvency risk. Furthermore, we also find that revenue diversification has positive impact on solvency risk and for opposite side, it has negative impact on credit risk. Next, bank age has positive impact solvency risk and it has negative impact on credit risk. Moreover, we also find that bank age moderated the relationship between asset diversification and credit risk. However, we can not support that bank age moderated the relationship revenue diversification and bank risk that measured by solvency risk and credit risk. Finally, we investigate bank-specific variables that determine bank risk which are bank size, receivable loss reserve ratio, cost to income ratio, profit margin ratio, and liquidity ratio